Legal Certainty of Lease Rights for Foreign Citizens of Ownership Land in Indonesia - Yudha Tri Dharma Iswara; Hanif Nur Widhiyanti; Novitasari Dian Ph (Jurnal Multidisiplin Madani, 2023)
In Indonesia, regulations have been issued that guarantee certainty over land in Indonesia, one of which is Law Number 5 of 1960 concerning the Basic Agrarian Law, which was subsequently reduced using Government Regulation Number 10 of 1961 concerning Land Registration and replaced with Government Regulation Number 24 of 1997 Concerning Land Registration, Foreign Citizens who have an interest in investing in Indonesia do a lot of land lease agreements, especially in Bali, because the term of a lease in Indonesia is not specifically regulated, law smuggling often occurs where a lease agreement has a long term, even indicating a lease for lifetime. Therefore the importance of a legal certainty regarding the lease term is regulated in a statutory regulation, so that in determining the term in the lease agreement it still has a decency and fairness in its implementation.The research method in this writing uses normative juridical law research with a statutory approach , legal concept approach  and case approach. In this thesis, the author discusses two legal issues related to legal certainty regarding the time limit for leasing private land in Indonesia for foreign nationals and the legal consequences arising from the ambiguity of legal norms regarding arrangements related to the time limit for leasing private land in Indonesia. The results of the research show that in terms of determining legal certainty related to the lease term for now, it can use or be based on the principle of decency in Article 1339 Kuperdata. The consequences that arise when a lease agreement has a time limit indicating a living well lease is a non-existent legal act